Dynapenia in all-cause mortality and its relationship with sedentary behavior in community-dwelling older adults - Rizia Rocha Silva; Lucas Lima Galvão; Joilson Meneguci; Douglas de Assis Teles Santos; Jair Sindra Virtuoso Júnior; Sheilla Tribess (Sports Medicine and Health Science, 2022)
The aim of the present study was to investigate the relationship of dynapenia combined with sedentary behavior (SB) on the risk of mortality in older adults living in a Brazilian community. A total of 322 participants aged ≥ 60 years from the ELSIA (Longitudinal Study of Elderly Health in Alcobaça) prospective cohort were included. Dynapenia was diagnosed when the handgrip strength was < 27 ​kg for men and < 16 ​kg for women. The exposure time to SB was assessed considering the total time spent sitting during one day in the week and one day on the weekend. When combined with dynapenia, we derived the construction of four groups: best behavior (absence of dynapenia and low SB), intermediate behavior (absence of dynapenia and high SB; presence of dynapenia and low SB) and worst behavior (presence of dynapenia and high SB). Mortality was assessed by the follow-up time until death and/or censorship. During the 5-year follow-up of the study, 55 participants progressed to death. In the adjusted models, the dynapenia and the time spent exposed to SB were analyzed in a combined way, the older adults with worse behavior (high SB and dynapenia) had higher risk ratios for mortality (hazard ratio 2.46; 95% confidence interval 1.01–5.97) than the best behavior group. Older adults with dynapenia are at greater risk for all-cause mortality, which is aggravated by the addition of longer exposure to SB.